Supermolecule-mediated defect engineering of porous carbons for zinc-ion hybrid capacitors. (1st December 2022) - Zhang, Wenli; Yin, Jian; Jian, Wenbin; Wu, Ying; Chen, Liheng; Sun, Minglei; Schwingenschlögl, Udo; Qiu, Xueqing; Alshareef, Husam N.
Abstract: Zinc ion hybrid capacitors hold great potential for future energy storage that requires both high energy density and high power capability. However, the charge storage mechanism of porous carbon cathode is ambiguous in Zn 2+ ion-containing aqueous solutions, albeit porous carbon usually stores charge by electric double-layer capacitance. Herein, we developed a supermolecule-mediated direct pyrolysis carbonization strategy to convert sustainable sodium lignosulfonate resources into three-dimensional highly heteroatom-doped porous carbons with large mesopores. Through this strategy, we obtained lignin-derived porous carbons with high heteroatom dopings (14.9 at% nitrogen and 4.7 at% oxygen) and relatively high specific surface areas. Furthermore, the nitrogen doping configurations were mainly edge-nitrogen dopants even under high pyrolysis temperatures (> 900 °C). Lignin-derived nitrogen-doped porous carbon showed a high gravimetric specific capacitance of 266 F g −1 with high rate capability, which is endowed by the increased surface pseudocapacitance. First-principles calculations and molecular dynamics simulations indicate that the edge nitrogen and oxygen dopants contribute to the reversible adsorption/desorption of zinc ions and protons. Pores size less than 6.8 Å can cause a significant diffusion energy barrier for the hydrated zinc ions, thus degrading the capacitance and rate capability. Graphical Abstract: ga1 Highlights: A novel supermolecule-mediated defect engineering was developed to prepare high-nitrogen doped porous carbons. Nitrogen and oxygen dopants contribute to the pseudocapacitance of porous carbon cathodes. The influence of pore size on the storage of Zn 2+ ions are investigated by molecular simulation methods.